Factors Affecting Adherence to Iron-Folic Acid Supplementation Among Adolescent Girls: An Integrative Review - Muhammad Hilmy As Shiddiq; Ima Arum Lestarini; Novia Andansari Putri Restuningdyah (Indonesian, 2025)
Adherence to Iron-Folic Acid (IFA) supplementation is a critical strategy in preventing and overcoming anemia among adolescent girls. However, compliance rates remain inconsistent across various regions. This integrative review aims to identify and synthesize the multi-dimensional factors influencing adherence to IFA supplementation among adolescent girls. A total of 28 relevant studies, including quantitative, qualitative, and systematic reviews, were analyzed. The findings indicate that adherence is determined by several key factors: (1) Individual factors, including knowledge of anemia, attitudes towards supplements, and personal motivation; (2) Social and environmental support, particularly the crucial roles of family (parents) and school environments (teacher supervision); and (3) Programmatic interventions, such as culture-based nutrition education and the use of digital health applications. Barriers such as fear of side effects and lack of consistent information were also identified. This review concludes that a multi-sectoral approach involving schools and families, supported by innovative educational media, is essential to improve compliance and ensure the success of anemia prevention programs.